Biological methane production under putative Enceladus-like conditions - Ruth-Sophie Taubner (Nature Portfolio, 2018)
Many methanogenic archaea use H2 and CO2 to produce methane. Here, Taubner et al. show that Methanothermococcus okinawensis produces methane under conditions extrapolated for Saturn’s icy moon, Enceladus, and estimate that serpentinization may produce sufficient H2 for biological methane production.